Hydrogen Storage and Selective, Reversible O2 Adsorption in a Metal–Organic Framework with Open Chromium(II) Sites. Issue 30 (1st June 2016) - Bloch, Eric D.; Queen, Wendy L.; Hudson, Matthew R.; Mason, Jarad A.; Xiao, Dianne J.; Murray, Leslie J.; Flacau, Roxana; Brown, Craig M.; Long, Jeffrey R.
Abstract: A chromium(II)‐based metal–organic framework Cr3 [(Cr4 Cl)3 (BTT)8 ]2 (Cr‐BTT; BTT 3− =1, 3, 5‐benzenetristetrazolate), featuring coordinatively unsaturated, redox‐active Cr 2+ cation sites, was synthesized and investigated for potential applications in H2 storage and O2 production. Low‐pressure H2 adsorption and neutron powder diffraction experiments reveal moderately strong Cr–H2 interactions, in line with results from previously reported M‐BTT frameworks. Notably, gas adsorption measurements also reveal excellent O2 /N2 selectivity with substantial O2 reversibility at room temperature, based on selective electron transfer to form Cr III superoxide moieties. Infrared spectroscopy and powder neutron diffraction experiments were used to confirm this mechanism of selective O2 binding. Abstract : Reversible O2 binding : A chromium(II)‐based metal–organic framework Cr3 [(Cr4 Cl)3 (BTT)8 ]2 (Cr‐BTT; BTT 3− =1, 3, 5‐benzenetristetrazolate) reversibly forms chromium(III) superoxide moieties, resulting in high separation capacity and reversibility for the separation of O2 from air at room temperature. Atom colors: Cr green, Cl purple, C gray, N blue.